After Effects CC in depth. (John Wiley & Sons, 2014)
"Master After Effects CC on your terms with this one-of-a-kind video training course. Adobe After Effects CC is one of the creative industry’s leading motion graphics and visual effects programs, and After Effects CC is packed with the tools you need to create videos, motion graphics, and 3D animation. With this video course you will go beyond the basics to maximize After Effects CC and start taking advantage of all the features that After Effects offers. Our instructors provide expert, straight-forward, user-friendly training to help you tackle After Effects CC the way you want to learn. First, this course will familiarize you with the newest features of After Effects CC. Then you’ll take a deep-dive into After Effects video effects tools. Learn advanced animation techniques, work with 3D effects, and understand how to share your project for various media. If you’re looking for real-world After Effects instruction, you’ll find it here."--Resource description page.